Мұстафа Шоқай — Қазақстан тəуелсіздігінің символдық тұлғасы ретінде - Каренов, Р.С. (ҚарМУ басп., 2012)
В статье отмечается, что Мустафа Чокай является одной из самых знаковых фигур первой половины XX в. не только в политической жизни Казахстана, но и всего тюркского мира. Подчеркивается, что без идеологической предвзятости о Чокае стали говорить только недавно, что ныне его деятельность получает все большее освещение в историографии постсоветского пространства. Анализируется на- учная, публицистическая деятельность Мустафы, который стал одним из первых политических эмиг- рантов, отстаивавших интересы тюркских народов. В научных и литературных трудах он писал о своей сокровенной мечте — единстве народов Туркестана. Автор показывает, что Мустафа блестяще справил- ся с отведенной ему историей ролью представителя тюркских народов в Европе, раскрывает современ- ное состояние изучения в нашей стране и за рубежом творческого наследия и научно-просветительской деятельности Мустафы Чокая. It is noticed that Mustafa Chokaj is one of the most sign figures of first half of XX-th century not only in political life of Kazakhstan, but also all Turkic world. It is underlined that without ideological bias about Chokae began to speak only recently. It is shown that nowadays its activity receives the increasing illumination in a post-Soviet territory historiography. Scientific, publicistic activity of Mustafy which became one of the first political refugees defending interests of the Turkic people is analyzed. It is proved that in the scientific and literary works he wrote about the secret dream — unity of the people of Turkestan. It is underlined that Mustafa has excellent coped with the history taken away to it a role of the representative of the Turkic people in Europe. The studying current state in our country and abroad a creative heritage and scientificallyeducational activity of Mustafy Chokaja reveals.